2003
DOI: 10.1111/1467-8624.00614
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Dynamic Field Theory: Working Memory for Locations Becomes More Spatially Precise Over Development

Abstract: The dynamic field theory predicts that biases toward remembered locations depend on the separation between targets, and the spatial precision of interactions in working memory that become enhanced over development. This was tested by varying the separation between A and B locations in a sandbox. Children searched for an object 6 times at an A location, followed by 3 trials at a B location. Two‐ and 4‐year‐olds', but not 6‐year‐olds', responses were biased toward A when A and B were 9‐in. and 6‐in. apart. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
206
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(219 citation statements)
references
References 48 publications
9
206
4
Order By: Relevance
“…In the past decade, we have shown that these phenomena can be brought under the same theoretical umbrella-the dynamic field framework-and that this framework can generate novel, testable predictions (Schutte, et al, 2003;Simmering & Spencer, 2007;Spencer, et al, 2007). Here we take this claim one step further by demonstratingfor the first time-that these phenomena can, in fact, be integrated within a single model (the 5-layer version of the DFT shown in Fig.…”
Section: Development In the Dftmentioning
confidence: 85%
See 1 more Smart Citation
“…In the past decade, we have shown that these phenomena can be brought under the same theoretical umbrella-the dynamic field framework-and that this framework can generate novel, testable predictions (Schutte, et al, 2003;Simmering & Spencer, 2007;Spencer, et al, 2007). Here we take this claim one step further by demonstratingfor the first time-that these phenomena can, in fact, be integrated within a single model (the 5-layer version of the DFT shown in Fig.…”
Section: Development In the Dftmentioning
confidence: 85%
“…We have previously captured behavioral changes across tasks and development within the dynamic field framework using a relatively simple developmental hypothesis-the spatial precision hypothesis (SPH, Schutte, Spencer & Schöner, 2003;Simmering & Spencer, 2007;Spencer & Hund, 2003;Spencer, et al, 2007). The SPH posits that neural interactions become stronger and more precise over development.…”
Section: Development In the Dftmentioning
confidence: 99%
“…Because the processes operating within the DFT to produce behavior are well-specified, there are a limited number of possible mechanisms to account for developmental increases in capacity. Previous work in spatial cognitive development established the SPH to account for development of children’s spatial recall biases (e.g., Schutte & Spencer, 2009), position discrimination performance (Simmering & Spencer, 2008), interactions between spatial working memory and long-term memory (Schutte et al, 2003), and perception of symmetry axes (Ortmann & Schutte, 2010). According to this hypothesis, neural interactions within and between layers in the model become stronger over development, purportedly through Hebbian learning and/or synaptogenesis (discussed further in Section 6; see also, e.g., Spencer et al, 2007).…”
Section: Modeling Change Detection Performance Over Developmentmentioning
confidence: 99%
“…This also highlights the importance of stability at different timescales: not only is an individual peak more susceptible to perturbation on an individual trial, but the variation in peak position and strength also varies considerably across trials early in development. Given the successful application to developmental changes in spatial cognition during early childhood (Ortmann & Schutte, 2010; Schutte & Spencer, 2009, 2010; Schutte et al, 2003; Simmering et al, 2008; Simmering & Spencer, 2008) and recent extensions to developmental changes in infant looking behavior (Perone et al, 2011; Perone & Spencer, 2011; Perone, Spencer, & Schöner, 2007), Simmering (2008) tested whether the SPH could also account for developmental increases in capacity.…”
Section: Modeling Change Detection Performance Over Developmentmentioning
confidence: 99%
See 1 more Smart Citation